TRAINING AND ASSISTANCE AN NISAA’ QURAN RECITATION GROUP RUNGKUT IN UTILIZING TANAMAN OBAT KELUARGA (TOGA) INTO HERBAL PRODUCTS - Rini Hamsidi; Dwi Setiani Sumardiko; Ilkafah Ilkafah; Edith Frederika Puruhito; Ratna Wahyuni; Maya Septriana; Myrna Adianti; Ario Imandiri; Taufiqurrahman Sidqi (Faculty of Vocational Studies, Universitas Airlangga, 2021)
Background: The corona virus pandemic (COVID-19) is spreading rapidly in a number of countries, including Indonesia. In order to deal with the increasingly widespread COVID-19, the government has established health and safety protocols by staying at home and maintaining distance, washing hands frequently with soap with running water or using hand sanitizers and increasing the body's immune system. One way to increase the immune system is through the use of Family Medicinal Plants (TOGA). Purpose: Transfer of knowledge and technology to An Nisaa 'study group partners through counseling on the use of TOGA by using appropriate technology to produce natural Hand Sanitizer products and instant herbal empon-empon in powder form which makes it easier to use daily. Methods: Methods of extension (lectures and discussions), training and mentoring using the Good Traditional Medicine Manufacturing Method (CPOTB) in producing natural Hand Sanitizer products and instant herbal medicine. Results: The expected result of this program is the use of TOGA by the community, especially partners to produce immune system-enhancing herbal products that are safe and can be stored for a long time to maintain health, especially families during the COVID 19 pandemic. Conclusion: This program increased knowledge and the skills of the An Nisaa 'Rungkut recitation group seen from the enthusiasm and ability of the participants in following and practicing the making of herbal medicine and hand sanitizers.